2020
DOI: 10.1021/acs.analchem.0c03557
|View full text |Cite
|
Sign up to set email alerts
|

Glass Fiber-Supported Hybrid Monolithic Spin Tip for Enrichment of Phosphopeptides from Urinary Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are attracting increasing interest with their intriguing role in intercellular communications. Protein phosphorylation in EVs is of great importance for understanding intercellular signaling processes. However, the study of EV phosphoproteomics is impeded by their relatively low amount in limited clinical sample volumes, and it is necessary to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…The final spin tip method provides identification performance similar to other methods working with milligram protein samples. However, there have recently been reported IMAC methods that are more complicated to use but can provide similar enrichment performance and selectivity to our optimized TiO 2 -based method [17][18][19].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The final spin tip method provides identification performance similar to other methods working with milligram protein samples. However, there have recently been reported IMAC methods that are more complicated to use but can provide similar enrichment performance and selectivity to our optimized TiO 2 -based method [17][18][19].…”
Section: Discussionmentioning
confidence: 86%
“…There are hardly any literature protocols available [16] for the TiO 2 -based phosphopeptide enrichment of sub-microgram complex samples like tissue microbiopsies, despite the fact that the above-mentioned methods are not directly applicable for these kinds of samples. However, there have been some IMAC methods providing satisfactory enrichment performance down to 1 µg of complex samples, yet posing the problem of moderate specificity [17][18][19]. Literature evidence and our experience suggested that the amount of the starting material and the analyte/stationary phase ratio was a major factor influencing the performance of the enrichment [20].…”
Section: Introductionmentioning
confidence: 95%
“…To characterize the protein composition of plasma EV preparations purified using Tymora’s non-antibody-based affinity EVtrap™ proprietary technology (designed to quantitatively capture membrane-bound vesicles including exosomes and validated in multiple peer-reviewed publications [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ), we assessed the enrichment in exosomal proteins curated by the ExoCarta Database. EVs were highly enriched in exosomal proteins, including 87 of the top 100 Exocarta proteins and nanoparticle tracking analysis (NTA) demonstrated size distributions consistent with preparations enriched in small EVs ( Figure 1 A-E).…”
Section: Resultsmentioning
confidence: 99%
“…EV purification was conducted as described by Nunez Lopez and colleagues [19] , using EVtrap™ (Tymora Analytical, Lafayette, IN, USA), a non-antibody- bead-based affinity technology developed to specifically and quantitatively isolate EVs. The EVtrap™ technology has been further described and validated in detail elsewhere [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . In short, frozen plasma samples were thawed and large debris removed by centrifugation at 2500×g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Monoliths can be manufactured using alternative components that confer different structural characteristics and provide a variety of active groups suitable for functionalization [ 14 ]. Silica and methacrylate monoliths have already been exploited for EV fractionation according to alternative chromatographic principles [ 15 , 16 , 17 ] and the sequential stacking of single methacrylate monolith elements activated with antibodies specific for different EV biomarkers that have succeeded in fractionating two EV sub-populations [ 18 ]. Monolith working capacity is independent of the element dimensions, but the cost of the affinity reagents necessary for its functionalization can rapidly become limiting during volume scaling-up.…”
Section: Introductionmentioning
confidence: 99%